ANALISIS PENGARUH ARUS DAN FAKTOR DAYA TERHADAP JATUH TEGANGAN PADA UJUNG PENGHANTAR SALURAN UDARA TEGANGAN MENENGAH PT. PLN ULP LIWA - Rizal, Rahman; Erhaneli, Erhaneli; Dewi, Arfita Yuana; Zulkarnaini, Zulkarnaini; Bandri, Sepannur (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Although Indonesia has a considerable potential for New Renewable Energy (EBT), its development has not yet reached the level necessary for future optimization. The Batang Merangin River in Kerinci Regency is a location where a Micro Hydro Power Plant (PLTMH) could be constructed. Calculating the potential output of electrical power is the goal of this study. In order to fully utilize the electrical energy potential in the area around the Batang Merangin River, this research will be very beneficial for achieving regional electricity independence. The PLTMH design, which specifies the kind of water turbine (Francis) and the size of the turbine, is based on the results of measuring the water output and the height of the water fall. The research approach that will be used is a planning approach that makes use of both field research and mathematical computations. The potential power generated is quite great if the created water discharge is sufficient. The research's findings led to a 5,278.272 kW power capacity with a 43.4 m-high water fall. With the right machinery and parts, the power produced improves as more water enters the turbine in the power plant. The study's findings suggest that the effectiveness of each PLTMH component should be prioritized while planning the PLTMH.Keywords : EBT, Microhydro, Electrical Energy, Flow Rate, Francis Type Water Turbine